Vena Cava Filters: Toward Optimal Strategies for Filter Retrieval and Patients' Follow-Up - Rezaei-Kalantari, Kiara; Rotzinger, David C.; Qanadli, Salah D. (Frontiers in Cardiovascular Medicine, 2022)
Mortality rates associated with venous thromboembolism (VTE) are high. Inferior vena cava filters (IVCFs) have been frequently placed for these patients as part of their treatment, albeit the paucity of data showing their ultimate efficacy and potential risk of complications. Issues regarding long-term filter dwell time are accounted for in society guidelines. This topic has led to an FDA mandate for filter retrieved as soon as protection from pulmonary embolism is no longer needed. However, even though most are retrievable, some were inadvertently left as permanent, which carries an incremental lifetime risk to the patient. In the past decade, attempts have aimed to determine the optimal time interval during which filter needs to be removed. In addition, distinct strategies have been implemented to boost retrieval rates. This review discusses current conflicts in indications, the not uncommon complications, the rationale and need for timely retrieval, and different quality improvement strategies to fulfill this aim.